2021
DOI: 10.1523/jneurosci.2939-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Effects of Oxytocin Neurons on Social Affiliation and Processing of Social Information

Abstract: Hormones regulate behavior either through activational effects that facilitate the acute expression of specific behaviors or through organizational effects that shape the development of the nervous system thereby altering adult behavior. Much research has implicated the neuropeptide oxytocin (OXT) in acute modulation of various aspects of social behaviors across vertebrate species, and OXT signaling is associated with the developmental social deficits observed in autism spectrum disorders (ASDs); however, litt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 101 publications
(117 reference statements)
0
21
0
Order By: Relevance
“…In a very recent study 74 , Nunes, Gliksberg and colleagues observed impaired social affiliation in adult zebrafish after chemical ablation of oxytocinergic neurons in the dorsorostral part of the neurosecretory preoptic area at early developmental stages (4–6 dpf and 12–14 dpf), but later ablation (20–22 dpf and 90 dpf) did not affect social preference of adult fish. As the ablated oxytocinergic neurons fully recovered within 42 days 74 , the described impaired social preference is likely due to the requirement of these oxytocinergic neurons at early developmental stages. The receptor knock-out fish we used in this study lacked Oxtr and Oxtrl, respectively, during all developmental stages.…”
Section: Discussionmentioning
confidence: 95%
“…In a very recent study 74 , Nunes, Gliksberg and colleagues observed impaired social affiliation in adult zebrafish after chemical ablation of oxytocinergic neurons in the dorsorostral part of the neurosecretory preoptic area at early developmental stages (4–6 dpf and 12–14 dpf), but later ablation (20–22 dpf and 90 dpf) did not affect social preference of adult fish. As the ablated oxytocinergic neurons fully recovered within 42 days 74 , the described impaired social preference is likely due to the requirement of these oxytocinergic neurons at early developmental stages. The receptor knock-out fish we used in this study lacked Oxtr and Oxtrl, respectively, during all developmental stages.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with this categorization, the PPa was recently implicated in zebrafish social behavior. Developmental oxytocin-cell ablation, which reduces social behavior, eliminates activation of the PPa by social stimuli ( Nunes et al, 2021 ). Our results now define a precise population of cells within the PPa that play a role in controlling social approach and orienting.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the knockout of one of the oxytocin receptors ( oxtr −/− or oxtrl −/−) enhanced the social preference level in zebrafish larvae at 3 and 4 weeks post fertilization [ 51 ]. Similarly, the early life ablation of oxytocin neurons led to a reduced social preference in adult zebrafish [ 113 ]. However, contrasting results in social behavior are obtained depending on the experimental design [ 49 , 51 , 114 ], which means it is more difficult to predict if an increase in oxytocin production will lead to increase or decrease in social preference.…”
Section: Discussionmentioning
confidence: 99%